Stem Cell Exosomes for Osteoarthritis in Veterinary Medicine - S. Amitha Banu; Khan Sharun; Rony S. Emmanuel; Merlin Mamachan; K. M. Manjusha; Sathish Muthu; Hussein M. El-Husseiny; Rohit Kumar; Abhijit M. Pawde; Kuldeep Dhama; null Amarpal (Stem Cells International)
Osteoarthritis (OA) is a growing health concern worldwide. This disease is a major concern in human and veterinary patients, especially in growing and geriatric individuals. The poor regenerative capacity of damaged cartilage affects the healing process. Currently, no effective treatment strategy exists that provides a complete cure. Despite several traditional and pharmacological treatments, none of them resulted in the repair and regeneration of cartilage tissue. Regenerative therapy has gained increasing attention in the treatment of OA as it is directly involved in the regenerative process of damaged cartilage. The mesenchymal stem cells (MSCs) have therapeutic potential in treating OA resulting from their paracrine action on host cells, mediated via cytokines, exosomes, growth factors, and extracellular matrix molecules. Even though no significant side effects are documented, cell-based therapeutics could still present some risks. Exosomes, on the other hand, act primarily by channelizing the resident cells to restore the damaged cartilage and thus play an essential role in the treatment of OA. This review explores the regenerative efficacy of exosomes in managing OA in veterinary patients, elucidating their mechanisms of action and therapeutic potential. Recognizing the importance of comprehending exosomes and their mechanisms is crucial for developing safe and effective cell-free therapeutics for OA. This paper aims to enhance our understanding of cell-free regenerative strategies, paving the way for the development of innovative treatments for OA in veterinary medicine.